НӨКИС ҚАЛАСЫНЫҢ ТАРИЙХЫНАН (1991-2005-жыллар) - Есназарова, З.Б. (FAN va JAMIYAT, 2025)
This articled is analyzed of historical-legal foundations in the development of the capital of Karakapakstan Republic. In the years of independence is founded the social life, covered the steps of formation. He basis of city life, economic and social - cultural development and we also filled up they history of Karakalpakstan in the sphere of city building and lead up in scientific operation of new factual materials.